Managing quality in construction: exploring challenges through project quality plan (pqp) implementation of the Klang Valley mass rapid transit (kvmrt) project - Azmi, Norfazliana; Hashim, Norfashiha; Hassan, Padzil @ Fadzil (GADING Journal for the Social Sciences, 2024)
The implementation of a Project Quality Plan (PQP) is often deemed a prerequisite in ensuring effective quality management in construction projects. However, issues related to quality persist despite its implementation. Hence, this study aims to investigate quality management challenges in constructions by emphasising obstacles in PQP implementation. Through a thorough exploration drawn from real-world experiences, the factors that hinder effective PQP applications were identified and analysed. Qualitative research methods were first employed, beginning with an extensive literature review to define the key conceptual elements of the project implementation process. Subsequently, face-to-face and phone/online interviews were conducted with quality managers that were subject matter experts to validate the identified elements. The data analysis utilised the ATLAS.ti software and followed by a multi-level thematic analysis process. Four key inhibiting factors of PQP implementation and quality management in a construction project were identified: (1) Inadequate exposure to PQP, (2) Vague process for operationalising PQP, (3) Lack of management commitment, and (4) Communication issues. These elements can offer actionable insights to practitioners to enhance project quality and contribute in the academic field by both increasing theoretical understanding and advancing practical project management activities. While the findings are limited to building construction and infrastructure works within the developing construction industry, such as Malaysia, this research provides valuable recommendations to guide practitioners in enhancing project quality and contributing to improvements in both theoretical understanding and practical project management activities.